HUBUNGAN PENGGUNAAN SOSIAL MEDIA, LINGKUNGAN KELUARGA, LINGKUNGAN SEKOLAH TERHADAP PEMAHAMAN NILAI-NILAI ISLAM SISWA SMA NEGERI KOTA PEKANBARU - Iqral, Muhammad (LP2M IAIN Sultan Amai Gorontalo, 2025)
Understanding Islamic values among students is a crucial aspect in shaping character and noble morals, especially in the digital era filled with various challenges. This study aims to analyze the influence of social media use, family environment, and school environment on students’ understanding of Islamic values. A quantitative approach was employed using a survey method at four public senior high schools (SMA) in Pekanbaru City, involving 363 students selected through accidental sampling. Data were collected using a structured questionnaire and analyzed through simple and multiple linear regression techniques. The results indicate that all three independent variables—social media use, family environment, and school environment—significantly affect the understanding of Islamic values, both partially and simultaneously. The family environment exerts the strongest influence (β = 0.389; p < 0.001), followed by social media use (β = 0.228; p < 0.001), and the school environment (β = 0.174; p = 0.001). Collectively, these variables contribute 50.7% to students' understanding of Islamic values (R² = 0.507). These findings underscore the importance of synergy among families, schools, and digital environments in strengthening the internalization of Islamic values. The implications of this study highlight the need for collaborative strategies among parents, educators, and policymakers to develop integrative Islamic value-based education programs.